Sosialisasi Bahaya Kekerasan Seksual Pada Perempuan Di Lingkungan Kampus Universitas Negeri Padang - Fitri, Fitri; Lisa Safitri; Nabila Coti; Yulia Hanoselina (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Sexual violence is an act that is carried out without consent, the many cases of sexual violence that occur today also occur in campus areas. This empowerment activity aims to provide understanding to women to be more sensitive to themselves and their surroundings by providing material on the forms of sexual violence that occur in the campus environment, the factors that cause it, and the prevention and handling efforts that are implemented. The forms of sexual violence are verbal, physical, and technology-based. Factors such as patriarchal culture, weak regulations, and power imbalances between lecturers and students are the main causes of sexual violence. The results of the activity with the topic "Socialization of the Dangers of Sexual Violence Against Women in the Campus Environment of Padang State University" showed an increase in student knowledge and awareness, with the hope of forming a campus culture that is more concerned and responsive to the issue of sexual violence.